The Role of Hypofractionated Radiation Therapy with Photons, Protons, and Heavy Ions for Treating Extracranial Lesions - Laine, Aaron Michael; Pompos, Arnold; Timmerman, Robert; Jiang, Steve; Story, Michael D.; Pistenmaa, David; Choy, Hak (Frontiers in Oncology, 2016)
Traditionally, the ability to deliver large doses of ionizing radiation to a tumor has been limited by radiation induced toxicity to normal surrounding tissues. This was the initial impetus for the development of conventionally fractionated radiation therapy, where large volumes of healthy tissue received radiation and were allowed the time to repair the radiation damage. However, advances in radiation delivery techniques and image guidance have allowed for more ablative doses of radiation to be delivered in a very accurate, conformal and safe manner with shortened fractionation schemes. Hypofractionated regimens with photons have already transformed how certain tumor types are treated with radiation therapy. Additionally, hypofractionation is able to deliver a complete course of ablative radiation therapy over a shorter period of time compared to conventional fractionation regimens making treatment more convenient to the patient and potentially more cost-effective. Recently there has been an increased interest in proton therapy because of the potential further improvement in dose distributions achievable due to their unique physical characteristics. Furthermore, with heavier ions the dose conformality is increased and in addition there is potentially a higher biological effectiveness compared to protons and photons. Due to the properties mentioned above, charged particle therapy has already become an attractive modality to further investigate the role of hypofractionation in the treatment of various tumors. This review will discuss the rationale and evolution of hypofractionated radiation therapy, the reported clinical success with initially photon and then charged particle modalities, and further potential implementation into treatment regimens going forward.